After the Bali agreement: Lessons from the Doha Round for the WTO's post-Bali agenda - Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2014)
At the WTO summit in Bali late last year, trade ministers managed to clear the way for a new trade agreement. This is positive news - and it proves that the WTO system is not dysfunctional. The Bali agreement brings new trading opportunities for developing countries and establishes a new standard for transparency in trade administration. But the Bali deal is not a Doha Round deal - it is not even a "Doha light" deal. Taking the cue from Coca Cola, it is closer to being a "Doha Zero" agreement. The idea that the Bali accord could build momentum for rejuvenating the entire Round, and get it to completion, is a bold one. The risks of failure are far greater than the chances of success. The post-Bali agenda should rather build on pragmatic approaches to negotiations while carving out new roles for the WTO as most trade negotiations for the rest of this decade will be non-multilateral. This paper surveys the structural problems that prevented Doha Round success and outlines some ideas for a new post-Bali agenda for the WTO. Some of the structural problems relate to broad changes in the structure of the world economy, others to the absence of political leadership or mercantilist workhorses to help push the Round to the finishing line. Furthermore, as the climate of ideas has been souring on economic liberalism for more than a decade any attempt to create more markets and less government in cross-border commerce would be challenging.
Keywords: 330; WTO-Verhandlungen